Clinical and etiological aspects of vulvovaginitis: a prospective and cross-sectional study from North India - Singla, Janvi; Puri, Aneesha; Puri, Suman; Sandhu, Jaspriya; Chaudhary, Muskan; Ladher, Heena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Vulvovaginitis is the inflammation and infection of the vulva and vagina, which commonly presents with itching, vaginal discharge and burning. It accounts for more than 30% of cases in healthcare clinics. Most common vaginal infections include bacterial vaginosis, trichomoniasis and vulvovaginal candidiasis. Accurate assessment of risk factors and diagnosis of vulvovaginitis are essential key to initiate effective management, thereby alleviating associated complications. This study was aimed to study the clinical and etiological aspects of vulvovaginitis. Methods: This was a tertiary care hospital based prospective cross-sectional study conducted on 250 women presenting with vulvovaginitis from January 2023 till August 2023. All patients presenting with vulvovaginitis were selected. Detailed history was taken. Demographic variables were assessed. Diagnosis was established based on clinical examination, microscopy, culture techniques and molecular assays. Results: Vulvovaginitis was seen commonly in married, multiparous women of reproductive age group, mostly in lower class strata. Common risk factors encountered were diabetes, douching, sanitary napkin reuse and amongst OCP users. Most common characteristics of vaginal discharge were greyish white, thin, scanty and associated with malodour. The most common cause leading to vulvovaginitis was bacterial vaginosis followed by vulvovaginal Candidiasis and Trichomoniasis. Conclusions: The reproductive age group was more susceptible to vulvovaginitis. Predisposing factors leading to vulvovaginitis included diabetes, multiple sexual partners, douching and sanitary napkin reuse. Bacterial vaginosis was the leading cause of vulvovaginitis (43.2%). Molecular tools may aid in the diagnosis of vulvovaginitis with unknown etiology. Primary prevention and timely diagnosis can avert complications and initiate treatment earlier.